2014
DOI: 10.1117/1.jbo.19.3.036015
|View full text |Cite
|
Sign up to set email alerts
|

Coregistered photoacoustic and ultrasonic signatures of early bone density variations

Abstract: This study examines the application of backscattered ultrasound (US) and photoacoustic (PA) signals for assessment of bone structure and density variations. Both methods were applied in the frequency-domain, employing linear frequency modulation chirps. A near-IR laser (800 nm) was used for inducing the PA signal. The backscattered pressure waves were detected with a 2.2-MHz US transducer. Experiments were focused on detection and evaluation of PA and US signals from in-vitro animal and human bones with cortic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 64 publications
0
24
0
Order By: Relevance
“…28 Recently, measurements of photoacoustic (PA) backpropagation from bones were reported for the first time. 30,31 Since PA is sensitive to the optical properties of tissue, it can detect composition variation and as such it can provide complementary information to US backscattering measurements. In our previous studies, we showed the sensitivity of PA with changes in minerals and organic phases of bone.…”
Section: Introductionmentioning
confidence: 99%
“…28 Recently, measurements of photoacoustic (PA) backpropagation from bones were reported for the first time. 30,31 Since PA is sensitive to the optical properties of tissue, it can detect composition variation and as such it can provide complementary information to US backscattering measurements. In our previous studies, we showed the sensitivity of PA with changes in minerals and organic phases of bone.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, photoacoustic (PA) imaging, an emerging hybrid technology involving both ultrasound and light, has been explored for potential application in the diagnosis of osteoporosis [3, 4]. Unlike QUS which is more sensitive to trabecular bone, PA signal is sensitive to the variations in bone density in both cortical and trabecular parts of the bone [3].…”
mentioning
confidence: 99%
“…Unlike QUS which is more sensitive to trabecular bone, PA signal is sensitive to the variations in bone density in both cortical and trabecular parts of the bone [3]. Multi-spectral PA signals from a biological sample can reflect the contents of the optically absorbing chemical components in the sample [4].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study has examined the possibility of PA to the evaluation of bone mineral concentration and microstructure [12][13][14]. Although the findings from this study are mostly qualitative, it demonstrates potential advantages of PA based bone evaluation over conventional US based technologies.…”
Section: Introductionmentioning
confidence: 80%